The process of acceptance and resilience of a mother with deaf child: Life history - Kurniawati, Dewi (Ittishal Educational Research Journal, 2023)
Every mother hopes to give birth to a perfect, normal, and healthy child, hope arises from the moment the child is still in the womb. Things turned around when the mother heard the diagnosis of her child with special needs. Various psychological problems experienced by mothers before finally reaching the stage of self-acceptance to be able to accept the state of themselves as mothers of children with special needs is a difficult process. Every mother has her own process and way to reach this stage. The purpose of this study was to see the picture, process, and factors of self-acceptance of mothers with children with special needs. This type of research uses qualitative with Life History. Data collection techniques use observation of family activities and interactions, in-depth interviews and document studies. Data collection was conducted from November 2022 to January 2023. The data obtained are analysed using thematic analysis techniques inductively. Based on the results of the study, the process towards maternal acceptance of deaf children begins with grief, anxiety. Self-acceptance is evidenced by the mother's adaptation process to master the situation, seek information, be sincere, think positively, and endeavour treatment. The process of self-acceptance is influenced by good family reciprocity, warm family support, good religious knowledge, and a supportive environment.